Nghiên cứu tổng hợp đồng kim loại có kích thước nano bằng phương pháp khử glyxerat trong vi sóng - Lộc, Đinh Xuân; Duy, Nguyễn Hoàng; Khanh, Phạm Duy; Bích, Lương Thị; Kiên, Ngô Trung; Tùng, Nguyễn Phương (Vietnam Journal of Chemistry, 2015)
Copper metal materials with nano size were successfully synthesized by copper glycerate reduction method in microwave. The technical analysis of morphology, structure and infrared spectroscopy of the materials were carried out. The morphology and the structure of the prepared materials were characterized by field emission scanning electron microscopy (FESEM) and X-ray diffraction (XRD). FESEM images and XRD patterns showed that the materials have phase single and the size of 60-100 nm. UV-VIS spectrum shows absorption peak at 595 nm.